Vine tourism south Africa - Chemen, Yuliia; Veres, Kateryna (My University, 2015)
Wine tourism is a new kind of tourism. It is developed in many countries, including Southern Africa. Country’s wine capital is the Western Cape. Tourists in this place can try a variety of wines, to visit local restaurants, as well as get acquainted with the culture of the country.
Keywords: wine tourism; Africa; винний туризм; Африка; кафедра туристичного та готельного бізнесу